Lack of vimentin impairs endothelial differentiation of embryonic stem cells - Boraas, Liana C. (Sci Rep, 2016)
The cytoskeletal filament vimentin is inherent to the endothelial phenotype and is critical for the proper function of endothelial cells in adult mice. It is unclear, however, if the presence of vimentin is necessary during differentiation to the endothelial phenotype. Here we evaluated gene and protein expression of differentiating wild type embryonic stem cells (WT ESCs) and vimentin knockout embryonic stem cells (VIM −/− ESCs) using embryoid bodies (EBs) formed from both cell types. Over seven days of differentiation VIM −/− EBs had altered morphology compared to WT EBs, with a rippled outer surface and a smaller size due to decreased proliferation. Gene expression of pluripotency markers decreased similarly for EBs of both cell types; however, VIM −/− EBs had impaired differentiation towards the endothelial phenotype. This was quantified with decreased expression of markers along the specification pathway, specifically the early mesodermal marker Brachy-T, the lateral plate mesodermal marker FLK1, and the endothelial-specific markers TIE2, PECAM, and VE-CADHERIN. Taken together, these results indicate that the absence of vimentin impairs spontaneous differentiation of ESCs to the endothelial phenotype in vitro.